Exploring the intersection of adverse childhood experiences and Attention-Deficit/Hyperactivity Disorder symptoms in adulthood: Differential vulnerability and resilience factors - Robertson, Sydney (Université d'Ottawa | University of Ottawa, 2025)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental disorder that persists into adulthood. Studies have shown that Adverse Childhood Experiences (ACEs) are associated with ADHD symptoms and emotional dysregulation. Additionally, research suggests that resilience factors may play a protective role on the impact of ACEs on ADHD symptoms and emotional dysregulation. This study investigates the relationship between ACEs with ADHD symptom severity and co-occurring Emotion Regulation (ER) in adults, and examines how resilience may moderate the association between ACEs and ADHD symptoms as well as ACEs and ER in adult populations. Three hundred and six participants between the ages of 18 to 55 years with diagnosed or high self-reported ADHD symptoms completed surveys measuring ADHD symptoms, ER, ACES, and resilience. Correlational analyses examined relationships between ADHD symptoms, ACES, ER, and resilience. Significant results showed a negative association between ACES and ER, ADHD symptoms and ER, and ACEs and resilience, along with a positive relationship between resilience and ER. Additionally, exploratory analyses demonstrated that ACEs were associated with the Predominantly Inattentive Presentation of ADHD, and that resilience specific to family cohesion and social resources were potential moderators. These findings highlight the complex interplay between ACEs, resilience, and ADHD symptoms.
Keywords: Attention-Deficit/Hyperactivity Disorder; ADHD; neurodevelopmental; Adverse Childhood Experiences; ACEs; Trauma; Resilience; Adult; Emotion Regulation; Protective; emotional dysregulation; symptoms